FDG PET/CT and MRI in Primary Spinal Cord Glioblastoma. (March 2020) - Shen, Guohua; Ma, Huan; Pan, Lili; Su, Minggang; Kuang, Anren
Abstract : Abstract: Glioblastoma is the most common primary malignant tumor of the central nervous system, most of which occur in the brain. Primary spinal cord glioblastoma is extremely rare. A 47-year-old woman presented with recurrent and progressive paresthesia and paralysis of right lower extremity. MR examination revealed a marked nodular enlargement of spinal cord at the T12 level, showing heterogeneous enhancement. FDG PET/CT showed this intraspinal lesion with high FDG uptake. Imaging findings indicated a possible diagnosis of malignant neoplasm. Surgical resection was performed, and the pathologic results confirmed a primary spinal cord glioblastoma.